Hookah smoking and cancer: carcinoembryonic antigen (CEA) levels in exclusive/ever hookah smokers - Chaouachi Kamal; Sajid Khan; Mahmood Rubaida (BMC, 2008)
Abstract Background We have recently published some work on CEA levels in hookah (also called narghile, shisha elsewhere) and cigarette smokers. Hookah smokers had higher levels of CEA than non-smokers although mean levels were low compared to cigarette smokers. However some of them were also users of other tobacco products (cigarettes, bidis, etc.). Objectives To find serum CEA levels in ever/exclusive hookah smokers, i.e. those who smoked only hookah (no cigarettes, bidis, etc.), prepared between 1 and 4 times a day with a quantity of up to 120 g of a tobacco-molasses mixture each (i.e. the tobacco weight equivalent of up to 60 cigarettes of 1 g each) and consumed in 1 to 8 sessions. Methods Enhanced chemiluminescent immunometric technique was applied to measure CEA levels in serum samples from 59 exclusive male smokers with age ranging from 20-80 years (mean = 58.8 ± 14.7 years) and 8-65 years of smoking (mean = 37.7 ± 16.8). 36 non-smokers served as controls. Subjects were divided into 3 groups according to the number of preparations; the number of sessions and the total daily smoking time: Light (1; 1; ≤ 20 minutes); Medium (1-3; 1-3; >20 min to ≤ 2 hrs) and Heavy smokers (2-4; 3-8; >2 hrs to ≤ 6 hrs). Because of the nature of distribution of CEA levels among our individuals, Wilcoxon's rank sum two-sample test was applied to compare the variables. Results The overall CEA levels in exclusive hookah smokers (mean: 3.58 ± 2.61 ng/ml; n = 59) were not significantly different (p ≤ 0.0937) from the levels in non-smokers (2.35 ± 0.71 ng/ml). Mean levels in light, medium and heavy smokers were: 1.06 ± 0.492 ng/ml (n = 5); 2.52 ± 1.15 ng/ml (n = 28) and 5.11 ± 3.08 ng/ml (n = 26) respectively. The levels in medium smokers and non-smokers were also not significantly different (p ≤ 0.9138). In heavy smokers, the CEA levels were significantly higher than in non-smokers (p ≤ 0.0001567). Conclusion Overall CEA levels in exclusive hookah smokers were low compared to cigarette smokers. However, heavy hookah smoking substantially raises CEA levels. Low-nitrosamines smokeless tobacco of the SNUS Swedish type could be envisaged as an alternative to smoking for this category of users and also, in a broad harm reduction perspective, to the prevalent low-quality moist snuff called naswar.